Pelatihan Sistem Akuntansi Keuangan Masjid (Sakmas) Di Kota Pekanbaru - M Rasuli; Julita Julita; Pipin Kurnia; Meilda Wiguna (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
A barrier of the mosque’s financial reporting is minimal knowledge of the financial management, limited sources of financial data, minimal of supporting infrastructure facilities, not having competent experts, non-productive human resources, and stutter of technology. Most mosques only have a financial record with a single-entry system. The majority of mosque managers are people who are still laymen with accounting. The application method used direct training to socialize ISAK 35 in the preparation of financial statements and provide training in the use of the mosque's financial accounting system (SAKMAS in accordance with IAK 35 on the presentation of financial statements to non-profit organizations). The Achievement level of success of the activity is the inception of the mosque's financial statements, understanding, and knowledge in training to make financial reporting in accordance with accounting standards. Each participant gets SAKMAS software that can be directly used. Moreover, the mosque can produce a double-entry recording system through SAKMAS. Takmir understanding increases into a good signal, thus increasing public confidence in the management of people's funds.